Manajemen Seni Pertunjukan Di Sanggar Puti Limo Jurai Kota Bukittinggi - Tiaranti Dwi Pradita; Darmawati Darmawati; Herlinda Mansyur (FBS Universitas Negeri Padang, 2019)
The research aims to describe the Management of the performing arts in the workshop of Puti Limo Jurai Bukittinggi. Type of this research is descriptive research using qualitative methods. The main instrument in this study is the researchers themselves and supporting instruments such as assisted with writing instruments and cameras. The type of the data in the research is the primary data and secondary data. Engineering data collection done by the study of librarianship, observation/observation, interview and documentation. Technique of data analysis performed with the measures include: the reduction of the data, the presentation of data, conclusions and make a report. The results showed that Sangar Puti Limo Jurai still retain cultural values in the performing arts. As an organization that is engaged in the arts with a democratic system, where all the decisions taken based on the results of the mutual agreement. All the process is carried out by management as good as possible. System performance or the workings of the organization performing arts at Sanggar Puti Limo Jurai belongs to the semi professional performing arts organizations because the Sanggar Puti Limo has been working with the Kings ' management approach, both in terms of function or process. In terms of personal profession, and the members of the Sanggar Puti Limo Emblem also has a profession other than the workers of art. But in terms of their ethics remain subject to rules that have been set.